2006
DOI: 10.1366/000370206777670585
|View full text |Cite
|
Sign up to set email alerts
|

Shining New Light on Old Principles: Localization of Evanescent Field Interactions at Infrared—Attenuated Total Reflection Sensing Interfaces

Abstract: A combined experimental and spectral ray tracing approach for identifying and evaluating evanescent field interactions with discrete surface deposits along a horizontal attenuated total reflection (HATR) element is presented. By experimentally depositing poly(styrene-co-butadiene) (PSCB) residues at fixed intervals along the measurement surface of a HATR crystal, distinct regions of evanescent field interaction with the surface deposits along the multi-reflection waveguide are visualized via infrared absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Hence, the resulting poly(SNS) films may have different thicknesses and different levels of polymerization yet during the same observation periods for the IR measurements. Furthermore, the IR measurement is subject to intensity variations across the ZnSe single bounce crystal surface in dependence of the area illuminated by the evanescent field 66. These factors are considered responsible for the fact that despite keeping the conditions for polymerizing each spot constant, variations in the IR signal are still observable.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the resulting poly(SNS) films may have different thicknesses and different levels of polymerization yet during the same observation periods for the IR measurements. Furthermore, the IR measurement is subject to intensity variations across the ZnSe single bounce crystal surface in dependence of the area illuminated by the evanescent field 66. These factors are considered responsible for the fact that despite keeping the conditions for polymerizing each spot constant, variations in the IR signal are still observable.…”
Section: Resultsmentioning
confidence: 99%
“…This approach allowed for simplifying the system, limiting bioactivity mechanisms only to the biofilm exposure towards metal ions. Previous studies showed the localization of IR-active sensing regions [64,69], helping to determine IR-inactive areas along the crystal surface; thus, we avoid infrared signals being convoluted with absorption intensity that might come from the composite film. The active spots were able to be attracted by the sampled biofilms as a consequence of exposure only to the Ag + ions released by the neighboring regions (3 mm spots of nanoantimicrobials, 0.5 mm thickness).…”
Section: Modification Of Znse Waveguide In Inactive Spotsmentioning
confidence: 99%
“…The deposition of the titanium|gold strips at the top and bottom portions of the waveguide resulted in an additional minor attenuation of the optical throughput, as radiation is confined mostly in the central portion of the waveguide. 83 Hence, despite substantial modification of the waveguide surface its optical transparency remains sufficient for spectroelectrochemical experiments (Fig. 5).…”
Section: Spectroelectrochemical Analysismentioning
confidence: 99%